Practical Problems of Social Teacher - Dobranskienė, Romualda (Acta Paedagogica Vilnensia, 2000)
While the department of social pedagogics was participating in the international TEMPUS project from 1995 to 1998, the experiments related to the need of social teachers and possibilities of professional functions and questions of professional preparation were held in Klaipėda region. The results of these experiments led to such the following conclusions: 1. All teachers need knowledge and experience of social work. Social teacher who is totally prepared and has obtained practical work experience is significantly needed not only for child care organizations but also for secondary education schools. Similarities and differences of class teacher's and social teacher’s activities were observed during the experiments and the possibilities of social teachers successful activities at secondary schools were analysed. 2. While preparing social teachers for educational and child care institutions, specialization is essential as well as specification of their meetings with different educational and care organizations. Special formation of the skills of social activities is essential for future social workers. Work practice, non-formal students’ activities and volunteers' work could help to establish this process. Course in the social work for preparation of social workers for educational institutions have to be closely related with practice. 3. It is necessary to evaluate norms of government social and educational institutions. (Extremely formal contacts between these institutions, with only occasional communications, as well as no interest or no care about further child’s fortune were identified). 4. Until now, little attention has been given to family problems in Lithuania. It is necessary to develop the initiatives and enthusiasm of future teachers. They need to be able fundamentally to help the child and the family, to reduce and eliminate the reasons for problems occurring. Future teachers need to take initiative and responsibility while creating social projects and implementing them. It is essential to develop the process of selection for future professionals in social pedagogics. Future social teachers need to have clear features of honesty, social skills and work experience. Therefore when accepting students to the social worker’s profession, not only the marks of their secondary school diploma should be considered but also personal characteristics and experience.
Keywords: Social teacher; school; practical problems; TEMPUS project.